Plane wave diffraction by a slit in an impedance plane and a complementary impedance strip - art. no. RS2022 - Çinar, G; Büyükaksoy, A (Amer Geophysical Union, 2004)
The diffraction of plane electromagnetic waves by the configuration formed by a slit in an impedance plane and a parallel complementary impedance strip is investigated. The related boundary value problem is formulated into two uncoupled modified Wiener-Hopf equations, which are first reduced to pairs of Fredholm integral equations of the second kind and then solved by iterations for large values of the electrical width kl of the slit. Several numerical results illustrating the effects of various parameters, such as the spacing between the slit and the strip, their widths, and surface impedances on the diffraction phenomenon, are presented.
Keywords: diffraction; slit; strip